Transformasi Promosi UMKM Tape Ketan dan Ubi Berbasis Hybrid: Efektivitas Pembuatan Spanduk dan Digitalisasi Lokasi pada Google Maps di Desa Balai Kasih - Ryan Rauzan; Amal Hayati; Tiara Devi Yanti Lestari; Fitri Khairani; Najwa Aulia Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
The Community Service Program (KKN) in Balai Kasih Village focuses on transforming the promotion of local Micro, Small, and Medium Enterprises (MSMEs) through a hybrid strategy that effectively combines traditional and digital media platforms. The selected target MSMEs in this program are Tape Ketan and Tape Ubi Pak Permadi, located specifically in Dusun IV. Prior to the intervention, these businesses lacked a clear location identity, official branding, and digital connectivity, which hindered customer accessibility and recognition. To address this issue, The KKN team facilitated the installation of informative identity banners and successfully registered the businesses on Google Maps on August 30, 2025. Using a participatory approach, this intervention demonstrated an increase in business visibility, making it easier for consumers to find locations online while strengthening trust at the local level. This study confirms that combining physical and digital promotion can improve the accessibility of village SMEs, open up broader market access, and provide a practical model for inclusive digital transformation-based economic empowerment.